Synthesis and characterization of PEDOT:PSS-co-TF for enhancing detection performances of organic photodetectors - Shen, Long; Seo, Gyeong Uk; Eun, Hyeong Ju; Prem, Prabhakaran; Yoon, Sang Eun; Kim, Jong H.; Kim, Tae Dong (Journal of Materials Chemistry C, 2023)
Poly(3,4-ethylenedioxythiophene) doped with poly (4-styrenesulfonate acid) (PEDOT:PSS), well-known as the most remarkable conducting polymer, has been applied in many areas due to its high electrical conductivity, high transparency, low cost, good flexibility and film formation property and excellent thermal stability. However, the strong acidity and insulating properties of PSS with high hydrophilicity can lead to significant deterioration of optoelectronic device performance. Here, we report the synthesis and study of fluorinated copolymers containing PSS called PSS-co-TF towards mitigating the above limitations. The resultant copolymers provide enhanced electrical conductivity and hydrophobicity to the PEDOT:PSS-co-TF composites compared to PEDOT:PSS even while sustaining good surface morphology. The influence of p-type buffer layers of PEDOT:PSS-co-TF composites on the performance of organic photodetectors made from poly(3-hexylthiophene) and PC[61]BM blends has been investigated. Among them, the device using PEDOT:PSS-co-TF3 exhibited the highest detectivity of 3.46 × 1012 Jones at −0.5 V in response to 510 nm light, attributed to the enhanced electrical conductivity.
Keywords: Detection performance; Electrical conductivity; Ethylenedioxythiophenes; High electrical conductivity; High transparency; Low-costs; Organics; PEDOT/PSS; Poly(4-styrenesulfonate); Synthesis and characterizations